PENGARUH KUALITAS PELAYANAN DAN PROMOSI TERHADAP LOYALITAS PELANGGAN PADA TOKO KOSMETIK SENJA KARAWANG - Najwa Khoerunnisa; Sinta Apriyani; Rahma Dini Aulia; Asep Maulana (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
ResearchThis research is entitled The Effect of Service Qualityand Promotion on Customer Loyalty at Senja Karawang Cosmetics Store.The factors tested in this study are service quality andpromotion as independent variables. Meanwhile, consumer loyalty is thedependent variable. The research method used in this study isquantitative. The population in this study is the residents of Karawang Regency.Sampling in this study used the simple randomsampling technique. The analyses used in this study included validity testing,reliability testing, classical assumption testing, multiple linear regression analysis, andhypothesis testing, which included t-testing, F-testing, and the coefficient of determination (R2). The resultsof this study indicate that service quality does not have a significant effecton customer loyalty, while promotion has a significant effectwith a significance level.